2010
DOI: 10.1007/s11141-010-9210-3
|View full text |Cite
|
Sign up to set email alerts
|

Artificial periodic irregularities, wave phenomena in the lower ionosphere, and the sporadic E layer

Abstract: We present new results of studying the artificial periodic irregularities produced in the ionosphere by the radio emission of the high-power heating facility "Sura" during the period of observations of the sporadic E layer. Basing on the measurement results for the velocity of the vertical plasma motion and the electron profile density in the E region of the ionosphere, which were obtained by the method of resonance scattering of radiowaves by an artificially produced periodic structure, we analyze the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…[] reported that decay times varied from a few milliseconds at the upper height (up to 140 km) for the few second at the lowest (80–90 km). Numerous API observations in D and E regions at Sura show the decay time of the same order as at HAARP [ Bakhmetieva and Belikovich , 2008; Bakhmetieva et al , , ]. Usually, APIs in the D and E regions existed throughout all experiments at the midlatitudes and show high variability of the echo amplitude at all heights.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…[] reported that decay times varied from a few milliseconds at the upper height (up to 140 km) for the few second at the lowest (80–90 km). Numerous API observations in D and E regions at Sura show the decay time of the same order as at HAARP [ Bakhmetieva and Belikovich , 2008; Bakhmetieva et al , , ]. Usually, APIs in the D and E regions existed throughout all experiments at the midlatitudes and show high variability of the echo amplitude at all heights.…”
Section: Discussionmentioning
confidence: 80%
“…[, , ]. The most recent experiments on the API formation were carried out using similar pumping and probing waves [ Bakhmet ' eva et al ., , , ; Bakhmetieva and Belikovich , , ; Grigoriev et al ., ; Tolmacheva et al ., ].…”
Section: Api Techniquementioning
confidence: 99%
See 3 more Smart Citations